Perjаnjiаn Pengikаtаn Juаl Beli sebagai Syаrаt Penerbitаn Denah Lokasi Perumаhаn - Dersanala, Nabilla Febrina; Wisnuwardhani, Diah Aju (Universitas Negeri Malang, 2022)
The focus of this study was to analyze the sale and purchase binding agreement as a condition for the issuance of a housing site plan and to analyze the position of the location plan issued based on the sale and purchase binding agreement. This study used a sociological juridical method with hermeneutic analysis techniques. The sale and purchase binding agreement could be used to fulfill the requirements for issuing a residential site plan while still attaching a deed of rights transfer from the land owner to the housing developer who submits the site plan application. The binding sale and purchase agreement could not be considered as proof of ownership of land rights but could be used as evidence that the developer had purchased land from the previous land owner. The position of the site plan issued based on the binding sale and purchase agreement was legal and could be accounted for as the basis for housing development by the developer.